An Analysis of Students' Difficulties in Speaking Ability; A Descriptive Study at Eleventh Students of SMA Islam Al-Ulum Medan: English - Encik Wanda Halizah; Fatimah Sari Siregar (Journal of English Development, 2024)
Abstract The purpose of this study was to examine the speaking ability faced by SMA Islam Al-Ulum Medan eleventh-grade high school students. The qualitative descriptive methodology is used in this study to examine the difficulties students have speaking. Questionnaires and classroom observations provided the data for this research. The information gathered shows that the main speaking challenges faced by eleventh-grade pupils might be broadly classified into two categories: linguistic and non-linguistic. According to information gathered from the questionnaire and in-class observations, students' primary language difficulties when speaking are related to a deficiency in vocabulary, mispronounced words, and inadequate knowledge of grammar. Non-linguistic elements like psychological ones don't play a big part in the primary challenges that pupils face when speaking English. However, many pupils struggle to speak fluently, which is a challenging task that requires the integration of linguistic and non-linguistic. Analyzing speaking difficulties that students encounter before or after learning English is essential.